Human NK Cell Subsets in Pregnancy and Disease: Toward a New Biological Complexity - Cristiani, Costanza Maria; Palella, Eleonora; Sottile, Rosa; Tallerico, Rossana; Garofalo, Cinzia; Carbone, Ennio (Frontiers in Immunology, 2016)
In humans, NK cells are mainly identified by the surface expression levels of CD56 and CD16, which differentiate between five functionally different NK cell subsets. However, nowadays NK cells are considered as a more heterogeneous population formed by various subsets differing in function, surface phenotype and anatomic localization. In HCMV- and hantaviruses-infected subjects, an increased frequency of a NKG2A- CD57+ NKG2C+ NK cell subset has been observed, while the phenotype of the NK cell subpopulation associated with cancer may vary according to the specific kind of tumor and its anatomical location. The healthy human lymph nodes contain mainly the CD56bright NK cell subset while in melanoma metastatic lymph nodes the CD56dimCD57+KIR+ CCR7+ NK cell subpopulation prevails. The five NK cell subpopulations are found in breast cancer patients, where they differ for expression pattern of chemokine receptors, maturation stage functional capabilities. In pregnancy, uterine NK cells show a prevalence of the CD56brightCD16- NK cell compartment, whose activity is influenced by KIRs repertoire. This NK cell subset’s super specialization could be explained by i) the expansion of single mature CD56dim clones, ii) the recruitment and maturation of CD56bright NK cells through specific stimuli, iii) the in situ development of tumor-resident NK cells from tissue-resident CD56bright NK cells independently of the circulating NK cell compartment. This new and unexpected biological feature of the NK cell compartment could be an important source of new biomarkers to improve patients’ diagnosis.